The identity of the type material of the subspecies of Melitaea phoebe ([Denis & Schiffermüller], 1775) described by Emilio Turati (Lepidoptera: Nymphalidae) - Peter J. C. Russell (SHILAP)
Two taxa described by Turati in 1920 as subspecies of Melitaea phoebe ([Denis & Schiffermüller], 1775), are examined from high resolution photographs. M. phoebe phoebina Turati, 1920 is identified from morphological features as M. ornata Christoph, 1893, and M. phoebe rostagnoi Turati, 1920, is confirmed as M. phoebe. The quadrinomial M. phoebe rostagnoi sterlineata Turati, 1920 from the same locality as subsp. rostagnoi is also confirmed as M. phoebe.